Understanding student errors in hydronym perception: a cognitive–pedagogical perspective - Akmaral Dautkulova; Mereke Atabayeva; Madiyeva Gulmira; Maxot Rakhmetov (International Journal of Evaluation and Research in Education (IJERE), 2026)
Despite the cultural and linguistic significance of hydronyms, little empirical research has examined how university students cognitively conceptualize them and why systematic misinterpretations arise. This study aims to identify and classify the dominant cognitive mechanisms underlying student errors in hydronym perception. A descriptive quantitative design was employed, analyzing written responses from 120 university students using a seven-category error typology grounded in frame semantics, prototype theory, and psycholinguistic models of proper-name processing, with high inter-rater reliability (κ=0.87). The results show that cognitive errors occur significantly more frequently than inattentive or interpretative errors, indicating that students’ difficulties stem primarily from incomplete activation of geographical, cultural, and historical conceptual frames rather than from surface-level inattention. Frequent reliance on phonological similarity further suggests that when conceptual knowledge is weakly integrated, learners’ default to form-based processing strategies instead of semantic interpretation. These findings indicate the need for pedagogical approaches that explicitly connect hydronyms to broader cultural and conceptual frameworks, supporting more cognitively grounded instruction in linguistics and onomastics.